PIII-induced enhancement and inhibition of human cell attachment on chitosan membranes - K. Inthanon (2018)
Chitosan membranes are good biodegradable materials for artificial organ applications. Treatment of the membrane surface with energetic ions can promote the application potential. Particular applications may require different properties of the material surface for cell attachment, either promoted or reduced. In this study, nitrogen and argon ions from plasma immersion ion implantation with bias of 5-10. kV were used to bombard chitosan membranes. Subsequent cell attachment using human cancer cells and normal fibroblast cells was investigated on the ion-treated membrane surfaces. Argon ions were found to have an enhancement effect on the cell attachment with increases in the cell attachment by about 20-30% and in the cell proliferation rate by 25% at most, whereas nitrogen ions had an inhibition effect on the cell growth with decreases in the cell attachment by about 5-30% and in the cell proliferation rate by 50-80%. Characterizations of the membranes on the contact angle, chemical bond, surface morphology and filopodia on the surface were carried out for discussion on relevant factors responsible for the cell attachment behavior. Ar-plasma treatment could increase the contact angle by 25% and the roughness by 10% compared with N-plasma treatment so that the cell filopodia migration could be favored. N-plasma treatment could break hydrogen and NH bonds compared with Ar-treatment and hence change the chemistry of the chitosan material. © 2012 Elsevier B.V.